A longitudinal investigation of non-suicidal self-injury persistence patterns, risk factors, and clinical outcomes during the college period - Kiekens, G.; Claes, L.; Hasking, Penelope; Mortier, P.; Bootsma, E.; Boyes, Mark; Myin-Germeys, I.; Demyttenaere, K.; Cuijpers, P.; Kessler, R.C.; Nock, M.K.; Bruffaerts, R. (CAMBRIDGE UNIV PRESS, 2023)
Background Although non-suicidal self-injury (NSSI) is known typically to begin in adolescence, longitudinal information is lacking about patterns, predictors, and clinical outcomes of NSSI persistence among emerging adults. The present study was designed to (1) estimate NSSI persistence during the college period, (2) identify risk factors and high-risk students for NSSI persistence patterns, and (3) evaluate the association with future mental disorders and suicidal thoughts and behaviors (STB). Methods Using prospective cohorts from the Leuven College Surveys (n = 5915), part of the World Mental Health International College Student Initiative, web-based surveys assessed mental health and psychosocial problems at college entrance and three annual follow-up assessments. Results Approximately one in five (20.4%) students reported lifetime NSSI at college entrance. NSSI persistence was estimated at 56.4%, with 15.6% reporting a high-frequency repetitive pattern (≥five times yearly). Many hypothesized risk factors were associated with repetitive NSSI persistence, with the most potent effects observed for pre-college NSSI characteristics. Multivariate models suggest that an intervention focusing on the 10-20% at the highest predicted risk could effectively reach 34.9-56.7% of students with high-frequency repetitive NSSI persistence (PPV = 81.8-93.4, AUC = 0.88-0.91). Repetitive NSSI persistence during the first two college years predicted 12-month mental disorders, role impairment, and STB during the third college year, including suicide attempts. Conclusions Most emerging adults with a history of NSSI report persistent self-injury during their college years. Web-based screening may be a promising approach for detecting students at risk for a highly persistent NSSI pattern characterized by subsequent adverse outcomes.